Technology Entrepreneurship (ENT600) Smart shoe cleaner machine / Muhammad Shameerul Afif Abd Halim, Muhammad Shameerul Akif Abd Halim and Luqman Arif Zurkarnain. - Abd Halim, Muhammad Shameerul Afif; Abd Halim, Muhammad Shameerul Akif; Zurkarnain, Luqman Arif (2017)
This smart shoe cleaner machine is an innovation idea to improvise the ordinary shoe brush that operated manually. This concept of idea basically to be a universal cleaning machine for any material and size of shoe. This product also will boost its business to spread widely through the worlds, as long as the people use the shoe to walk with clean and tidy. The target market should be larger, not only for ladies, but for all men too in the world. The smart shoe cleaner machine is suitable for any type of shoe, as it design to be a standard shape for all size and gender. Besides, people who travel around the world will be more easy to use this machine because it will widely use in the most country as an instant services machine. Thus, the focus for this smart shoe cleaner machine is projected on the potential customers such as executive person, streetwear fashion, travelers and kids too. This shoe cleaner machine combine with the rotor brush and dryer to give a complete services for all shoe user. Thus, it will be much helpful for workers, student and traveler to maintain their shoe clean and tidy all the time. Definitely, a great product comes from the great management team, which must be consisting of a proactive leader, a creative product designer, a hardworking market analyst and also the smart entrepreneur. Then the whole combination of vital skills in management will make this smart shoe cleaner machine becoming a new world class product.